2015
DOI: 10.1093/intqhc/mzv100
|View full text |Cite
|
Sign up to set email alerts
|

Incident and error reporting systems in intensive care: a systematic review of the literature

Abstract: None of the IRSs completely fulfilled the WHO checklist criteria. With respect to the iterative loop, data input and data collection are well established but not much attention was given to analyzing incidents and to give feedback. This resulted in an administrative report system, rather than the much desired instrument for change of practice and increase of quality as an IRS can only effectively contribute to improve patient safety and quality of care if more attention is given to analyzing incidents and feed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
61
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(67 citation statements)
references
References 65 publications
4
61
0
2
Order By: Relevance
“…Licensed registered nurses who worked in an adult intensive care unit (ICU) as direct patient caregivers comprised the study sample. ICUs were chosen because high rates of errors are reported on nursing units that provide acute care for critically ill patients, such as intensive care units (Brunsveld-Reinders, Arbous, De Vos, & De Jonge, 2016;Landrigan et al, 2004), and critically ill patients experience higher rates of adverse events and errors than other patient populations (Balas, Scott, & Rogers, 2006;Kiekkas, Karga, Lemonidou, Aretha, Karanikolas, 2011).…”
mentioning
confidence: 99%
“…Licensed registered nurses who worked in an adult intensive care unit (ICU) as direct patient caregivers comprised the study sample. ICUs were chosen because high rates of errors are reported on nursing units that provide acute care for critically ill patients, such as intensive care units (Brunsveld-Reinders, Arbous, De Vos, & De Jonge, 2016;Landrigan et al, 2004), and critically ill patients experience higher rates of adverse events and errors than other patient populations (Balas, Scott, & Rogers, 2006;Kiekkas, Karga, Lemonidou, Aretha, Karanikolas, 2011).…”
mentioning
confidence: 99%
“…The resident physicians in this study similarly wanted feedback about their incidents that they could apply to actual practice to benefit their work. Feedback on incident reports has been shown to have a positive effect on reporting, so organizations should recognize its importance …”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis has shown that only a few Incident Reporting Systems (IRS) employed in critical care settings contain all elements suggested by the WHO checklist. 16 This analysis showed that the data input and collection systems are well established and aligned with the checklist. Nevertheless, among the major identified deficiencies of the existing IRS is the lack of a consistent approach to the analysis of incidents.…”
mentioning
confidence: 92%